Positive electrode active material, preparation method thereof and secondary battery
By using a combination of sodium-layer oxide, selenium-antimony compound and carbon in the positive electrode active material, the structural stability and performance problems of the material in sodium ion batteries are solved, and higher sodium storage capacity and cycle stability are achieved .
Patent Information
- Application Number
- CN202411257512.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The sodium storage capacity, cycle stability and rate performance of positive electrode active materials in sodium ion batteries is poor, mainly because transition metal layered oxides are prone to phase transformation and structural degradation during the deintercalation process.
The positive electrode active material is prepared through a sintering process using a combination of sodium layered oxide, selenium-antimony compound and carbon. The selenium-antimony compound is melted into secondary particles and evenly dispersed. The carbon material enhances the conductivity and reduces internal mechanical stress and side reactions.
The cyclic stability and rate performance of the positive electrode material are significantly improved, intergranular cracking and electrolyte side reactions are suppressed, and the capacity and electrical performance of sodium storage are improved.
Smart Images

Figure BDA0005034531680000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a positive electrode active material and a preparation method thereof and a secondary battery. Background Art
[0002] In recent years, global environmental problems have become increasingly severe, and the development of new renewable energy sources has become urgent. As the most promising sustainable energy source, lithium-ion batteries are widely used in various portable mobile devices, electric vehicles, energy storage and other fields due to their high safety, high energy density, and long service life. However, due to the extremely uneven distribution of lithium resources around the world and the current rapid and large-scale consumption, the production and use costs will inevitably be greatly affected. Sodium-ion batteries have received widespread attention in the global energy storage field due to their wide distribution of sodium resources.
[0003] As a key link in the entire battery system, the positive electrode material plays a decisive role in the entire battery system in terms of cycle stability, output voltage, thermal stability, output capacity, power density and other indicators. x TmO2 (Tm is a transition element, 0<x≤1) has the potential to become a candidate material for the positive electrode of sodium-ion batteries due to its advantages such as high specific capacity, simple preparation method, and reversible deintercalation. However, this material is prone to phase change during the deintercalation process, resulting in structural deformation and degradation. The reversible capacity decays severely during the cycle process, resulting in poor sodium storage capacity, cycle stability and high-rate performance.
[0004] Therefore, how to effectively optimize and modify the positive electrode active material to improve its sodium storage capacity, cycle stability and rate performance is one of the technical problems that need to be urgently solved in this field. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing a positive electrode active material to solve the problems of poor sodium storage gram capacity, cycle stability and high rate performance.
[0006] The present invention also provides a positive electrode active material prepared by the above preparation method.
[0007] In a first aspect, the present invention provides a positive electrode active material comprising a sodium-containing layered oxide, a selenium antimony compound and carbon.
[0008] In an optional embodiment, based on the mass of the sodium-containing layered oxide, the mass percentage of selenium is 500ppm-15000ppm.
[0009] In an optional embodiment, based on the mass of the sodium-containing layered oxide, the mass percentage of antimony element is 200 ppm-15500 ppm.
[0010] In an optional embodiment, based on the mass of the sodium-containing layered oxide, the mass percentage of carbon element is 700ppm-20000ppm.
[0011] In an optional embodiment, the selenium antimony compound includes at least one of antimony selenide, antimony selenium sulfide, and selenoantimonate.
[0012] In an optional embodiment, the sodium-containing layered oxide comprises a general chemical formula of NaNi x Fe y Mn z O2 material, wherein 0<x<0.5, 0<y<0.5, 0<z<0.5, x+y+z=1.
[0013] In an optional embodiment, the sodium-containing layered oxide further includes additive elements.
[0014] In an optional embodiment, the additive element includes at least one of magnesium, aluminum, strontium, tungsten and yttrium.
[0015] In an optional embodiment, based on the mass of the sodium-containing layered oxide, the mass percentage of the additive element is 500ppm-10000ppm.
[0016] In a second aspect, the present invention provides a method for preparing a positive electrode active material, comprising the following steps: mixing the sodium-containing layered oxide with a selenium antimony compound and a carbon source and then sintering once to obtain a positive electrode active material.
[0017] In an optional embodiment, based on the mass of the sodium-containing layered oxide, the mass percentage of the selenium antimony compound is 1000ppm-30000ppm.
[0018] In an optional embodiment, the mass percentage content of the carbon source is 1000ppm-20000ppm.
[0019] In an optional embodiment, the primary sintering temperature is 600° C.-1000° C., the sintering time is 6 h-20 h, and the sintering atmosphere is an inert gas.
[0020] In an optional embodiment, the selenium antimony compound includes at least one of antimony selenide, antimony selenium sulfide, and selenoantimonate.
[0021] In an optional embodiment, the chemical formula of antimony selenide is Sb2(S a ,Se 1-a )3, where 0<a<1.
[0022] In an optional embodiment, the selenoantimonate comprises V(1,2-dap)2SbSe3, C6H 20 At least one of N4SbSe3V, M2Sb(SeO4)3; wherein M includes at least one of Na and K.
[0023] In an optional embodiment, the carbon source includes at least one of glucose, sucrose, soluble starch, cellulose, graphene, carbon nanotubes, conductive carbon black, and acetylene black.
[0024] In an optional embodiment, the method for preparing the sodium-containing layered oxide comprises: mixing a sodium source with a ternary precursor and an additive and then performing secondary sintering.
[0025] In an optional embodiment, the sodium source is calculated as sodium element, and the molar ratio of the sodium element to the ternary precursor is 0.8-1.6:1.
[0026] In an optional embodiment, the sodium source includes at least one of sodium carbonate, sodium nitrate, sodium hydroxide, and sodium sulfate.
[0027] In an optional embodiment, based on the mass of the ternary precursor, the additive is calculated as an additive element, and the mass percentage of the additive element is 500ppm-10000ppm.
[0028] In an optional embodiment, the additive includes at least one of oxides or hydroxides or salts of magnesium, aluminum, strontium, tungsten, and yttrium.
[0029] In an optional embodiment, the chemical formula of the ternary precursor is Ni x Fe y Mn z (OH)2, where 0<x<0.5, 0<y<0.5, 0<z<0.5, x+y+z=1.
[0030] In an optional embodiment, the secondary sintering temperature is 600° C.-1000° C., the sintering time is 6 h-14 h, and the sintering atmosphere is air.
[0031] In a third aspect, the present invention provides a positive electrode plate, comprising: a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the above-mentioned positive electrode active material.
[0032] In a fourth aspect, the present invention provides a secondary battery comprising the above-mentioned positive electrode plate.
[0033] In a fifth aspect, the present invention provides an electrical device comprising the above-mentioned secondary battery.
[0034] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0035] 1. The positive electrode active material provided by the present invention comprises sodium-containing layered oxides, selenium antimony compounds and carbon. The Sb element of the present invention can induce radially oriented primary particles, effectively reduce internal mechanical stress, thereby hindering the development and diffusion of micro-scars, inhibiting intercrystalline cracking, enhancing the structural stability of the material, and improving the rate performance and cycle stability of the material; the Se element in situ covers the primary particles and secondary particles in the form of Se-like compounds, which is beneficial to reduce the side reactions between the electrolyte and the positive electrode, inhibit the dehydrogenation of common organic solvents in the electrolyte, and significantly improve the cycle performance of the positive electrode material;
[0036] The present invention adds carbon material to enhance the conductivity between particles, reduce battery polarization, and inhibit the growth of grains, thereby refining the grains and shortening the Na + The diffusion path inside the particle improves the material's rate performance.
[0037] 2. The positive electrode active material provided by the present invention, the sodium-containing layered oxide also includes at least one of magnesium, aluminum, strontium, tungsten and yttrium, which can improve the electrical properties of the positive electrode active material.
[0038] 3. In the method for preparing the positive electrode active material provided by the present invention, when the sodium-containing layered oxide and the selenium-antimony compound are calcined together, the selenium-antimony compound can be melted into secondary particles and dispersed more evenly on the surface of the positive electrode material particles.
[0039] 4. The preparation method of the positive electrode active material provided by the present invention limits the addition amount of selenium antimony compound to 1000ppm-30000ppm of the sodium-containing layered oxide; the addition amount of carbon source is 1000ppm-20000ppm of the sodium-containing layered oxide, which can significantly improve the capacity, rate performance and cycle stability of the material. DETAILED DESCRIPTION
[0040] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0041] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0042] In order to solve the problems existing in the above-mentioned related technologies, according to the first aspect of the present invention, the present invention provides a positive electrode active material, including a sodium-containing layered oxide, a selenium antimony compound and carbon; based on the mass of the sodium-containing layered oxide, the mass percentage of selenium element is 500ppm-15000ppm, the mass percentage of antimony element is 200ppm-15500ppm, and the mass percentage of carbon element is 700ppm-20000ppm; the selenium antimony compound includes at least one of antimony selenide, antimony selenide sulfide, and selenium antimonate; the sodium-containing layered oxide contains a chemical formula of NaNi x Fe y Mn z O2 material, wherein 0<x<0.5, 0<y<0.5, 0<z<0.5, x+y+z=1; the sodium-containing layered oxide also includes additive elements; the additive elements include at least one of magnesium, aluminum, strontium, tungsten and yttrium; based on the mass of the sodium-containing layered oxide, the mass percentage of the additive elements is 500ppm-10000ppm.
[0043] The Sb element of the present invention can induce radially oriented primary particles, effectively reduce internal mechanical stress, thereby hindering the development and diffusion of micro-scars, inhibiting intercrystalline cracking, enhancing the structural stability of the material, and improving the rate performance and cycle stability of the material; the Se element in situ covers the primary particles and secondary particles in the form of Se-like compounds, which is beneficial to reducing the side reactions between the electrolyte and the positive electrode, inhibiting the dehydrogenation of common organic solvents in the electrolyte, and significantly improving the cycle performance of the positive electrode material;
[0044] The present invention adds carbon material to enhance the conductivity between particles, reduce battery polarization, and inhibit the growth of grains, thereby refining the grains and shortening the Na + The diffusion path inside the particle improves the material's rate performance.
[0045] In a second aspect, the present invention provides a method for preparing a positive electrode active material, comprising the following steps:
[0046] (1) Weighing a sodium source, a ternary precursor, and an additive, mixing them, calcining them at 600° C. to 1000° C. in an air atmosphere for 6 h to 14 h, crushing and sieving, and obtaining a sodium-containing layered oxide. The sodium-containing layered oxide contains a chemical formula of NaNi x Fe y Mn zO2 material, 0<x<0.5, 0<y<0.5, 0<z<0.5, x+y+z=1; wherein, based on the mass of the ternary precursor, the additive is calculated as the additive element, the mass percentage of the additive element is 500ppm-10000ppm, and the molecular formula of the ternary precursor is Ni x Fe y Mn z (OH)2, wherein 0<x<0.5, 0<y<0.5, 0<z<0.5, x+y+z=1; the sodium source is calculated as sodium element, and the molar ratio of the sodium element to the ternary precursor is 0.8-1.6:1; the sodium source includes at least one of sodium carbonate, sodium nitrate, sodium hydroxide, and sodium sulfate; the additive includes at least one of the oxides, hydroxides, or salts of magnesium, aluminum, strontium, tungsten, and yttrium;
[0047] (2) mixing the sodium-containing layered oxide, the selenium antimony compound and the carbon source, calcining the mixture at 600° C.-1000° C. for 6 h-20 h in an inert atmosphere, and crushing and sieving the mixture to obtain a positive electrode material for a sodium ion battery; wherein the mass percentage of the selenium antimony compound is 1000 ppm-30000 ppm based on the mass of the sodium-containing layered oxide; the mass percentage of the carbon source is 1000 ppm-20000 ppm; the selenium antimony compound comprises at least one of antimony selenide, antimony selenide sulfide and selenoantimonate; the chemical formula of antimony selenide sulfide is Sb2(S a ,Se 1-a )3, wherein 0<a<1; selenoantimonates include V(1,2-dap)2SbSe3, C6H 20 At least one of N4SbSe3V, M2Sb(SeO4)3; wherein M includes at least one of Na and K; the carbon source includes at least one of glucose, sucrose, soluble starch, cellulose, graphene, carbon nanotubes, conductive carbon black, and acetylene black.
[0048] When the sodium-containing layered oxide and the selenium-antimony compound are calcined together, the selenium-antimony compound can be melted into secondary particles and dispersed more evenly on the surface of the positive electrode material particles.
[0049] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0050] Example 1
[0051] This embodiment provides a method for preparing a positive electrode active material, comprising the following steps:
[0052] (1) Weigh sodium carbonate and ternary precursor Ni 1 / 3 Fe 1 / 3 Mn 1 / 3(OH)2, magnesium hydroxide and aluminum hydroxide are mixed and calcined at 850°C for 12 hours in a compressed air atmosphere, and then crushed and sieved to obtain a sodium-containing layered oxide. The sodium-containing layered oxide contains NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 materials; wherein magnesium hydroxide is calculated as magnesium element, aluminum hydroxide is calculated as aluminum element, the addition amount of magnesium element and aluminum element is 1000ppm of the mass of the ternary precursor, and the molar ratio of sodium carbonate to the ternary precursor is 0.55:1; based on the mass of the sodium-containing layered oxide, the mass percentage content of the additive magnesium element and aluminum element is 1000ppm;
[0053] (2) The above-mentioned sodium-containing layered oxide, antimony selenide (Sb2Se3) and glucose are mixed and calcined at 750°C for 12 hours in a nitrogen atmosphere; wherein the added amount of Sb2Se3 and glucose is 10000ppm of the sodium-containing layered oxide; and the mixture is crushed and sieved to obtain a positive electrode active material, wherein, based on the mass of the sodium-containing layered oxide, the mass percentage of selenium element is 4930ppm, the mass percentage of antimony element is 5070ppm, and the mass percentage of carbon element is 4000ppm.
[0054] Example 2
[0055] This embodiment provides a method for preparing a positive electrode active material, comprising the following steps:
[0056] (1) Weigh sodium nitrate and ternary precursor Ni 0.4 Fe 0.45 Mn 0.15 (OH)2, magnesium sulfate, strontium chloride and tungsten oxide are mixed and calcined at 600℃ for 14h in a compressed air atmosphere, and then crushed and sieved to obtain a sodium-containing layered oxide. The sodium-containing layered oxide contains NaNi 0.4 Fe 0.45 Mn 0.15 O2 material; wherein, magnesium sulfate is calculated as magnesium element, strontium chloride is calculated as strontium element, tungsten oxide is calculated as tungsten element, the addition amount of magnesium element is 1000ppm of the mass of the ternary precursor, the addition amount of strontium element is 2500ppm of the mass of the ternary precursor, the addition amount of tungsten element is 1500ppm of the mass of the ternary precursor, and the molar ratio of sodium nitrate to the ternary precursor is 0.8:1; based on the mass of the sodium-containing layered oxide, the mass percentage content of the additive magnesium element is 1000ppm, the mass percentage content of the additive strontium element is 2500ppm, and the mass percentage content of the additive tungsten element is 1500ppm;
[0057] (2) The above sodium-containing layered oxide, antimony selenide sulfide (Sb2 (S 0.07 ,Se 0.93)3) After mixing sucrose and carbon nanotubes, calcinate them at 1000°C for 6 hours in a nitrogen atmosphere; wherein the amount of antimony selenium sulfide added is 20000ppm of the sodium-containing layered oxide, the amount of sucrose added is 5000ppm of the sodium-containing layered oxide, and the amount of carbon nanotubes added is 15000ppm of the sodium-containing layered oxide; crush and sieve to obtain a positive electrode active material; wherein, based on the mass of the sodium-containing layered oxide, the mass percentage of selenium element is 9000ppm, the mass percentage of antimony element is 10140ppm, and the mass percentage of carbon element is 17100ppm.
[0058] Example 3
[0059] This embodiment provides a method for preparing a positive electrode active material, comprising the following steps:
[0060] (1) Weigh sodium hydroxide and ternary precursor Ni 0.25 Fe 0.35 Mn 0.4 (OH)2, aluminum hydroxide and yttrium oxide are mixed and calcined at 1000℃ for 6h in a compressed air atmosphere, and then crushed and sieved to obtain a sodium-containing layered oxide. The sodium-containing layered oxide contains NaNi 0.25 Fe 0.35 Mn 0.4 O2 material; wherein aluminum hydroxide is calculated as aluminum element, yttrium oxide is calculated as yttrium element, the addition amount of aluminum element is 2500ppm of the mass of the ternary precursor, the addition amount of yttrium element is 1500ppm of the mass of the ternary precursor, and the molar ratio of sodium hydroxide to the ternary precursor is 1.3:1; based on the mass of the sodium-containing layered oxide, the mass percentage content of the additive aluminum element is 2500ppm; the mass percentage content of the additive yttrium element is 1500ppm;
[0061] (2) The sodium-containing layered oxide, selenoantimonate (V(1,2-dap)2SbSe3), graphene, soluble starch and acetylene black are mixed and calcined at 600°C for 20 hours in a nitrogen atmosphere; wherein the amount of selenoantimonate added is 1000ppm of the sodium-containing layered oxide, the amount of graphene added is 5000ppm of the sodium-containing layered oxide, the amount of soluble starch added is 7000ppm of the sodium-containing layered oxide, and the amount of acetylene black added is 3000ppm of the sodium-containing layered oxide; the mixture is crushed and sieved to obtain a positive electrode active material; wherein, based on the mass of the sodium-containing layered oxide, the mass percentage of selenium element is 500ppm, the mass percentage of antimony element is 250ppm, and the mass percentage of carbon element is 11100ppm.
[0062] Example 4
[0063] This embodiment provides a method for preparing a positive electrode active material, comprising the following steps:
[0064] (1) Weigh sodium sulfate and ternary precursor Ni 0.4 Fe 0.2 Mn 0.4 (OH)2 and ammonium metatungstate are mixed and calcined at 800℃ for 10h in a compressed air atmosphere, and then crushed and sieved to obtain a sodium-containing layered oxide. The sodium-containing layered oxide contains NaNi 0.4 Fe 0.2 Mn 0.4 O2 material; wherein, ammonium metatungstate is calculated as tungsten element, the amount of tungsten element added is 500ppm of the mass of the ternary precursor, the molar ratio of sodium sulfate to the ternary precursor is 0.4:1; based on the mass of the sodium-containing layered oxide, the mass percentage of the additive tungsten element is 500ppm;
[0065] (2) The above sodium-containing layered oxide, antimony selenide sulfide (Sb2 (S 0.07 ,Se 0.93 )3) Mix cellulose and conductive carbon black and calcine them at 850°C for 16 hours in a nitrogen atmosphere; wherein the amount of antimony selenium sulfide added is 30,000 ppm of the sodium-containing layered oxide; the amount of cellulose and conductive carbon black added is 500 ppm of the sodium-containing layered oxide; grind and sieve to obtain a positive electrode active material; wherein, based on the mass of the sodium-containing layered oxide, the mass percentage of selenium element is 13,500 ppm, the mass percentage of antimony element is 15,210 ppm, and the mass percentage of carbon element is 720 ppm.
[0066] Comparative Example 1
[0067] This comparative example provides a method for preparing a positive electrode active material, which is substantially the same as the steps of Example 1, except that step (2) is omitted.
[0068] Comparative Example 2
[0069] This comparative example provides a method for preparing a positive electrode active material, which is substantially the same as the steps of Example 1, except that, in step (2), the addition of antimony selenide is omitted.
[0070] Comparative Example 3
[0071] This comparative example provides a method for preparing a positive electrode active material, which is substantially the same as the steps of Example 1, except that antimony selenide is replaced by selenium oxide with the same selenium content and antimony oxide with the same antimony content.
[0072] Comparative Example 4
[0073] This comparative example provides a method for preparing a positive electrode active material, which is substantially the same as the steps of Example 1, except that the amount of Sb2Se3 added is 500 ppm of the sodium-containing layered oxide.
[0074] Comparative Example 5
[0075] This comparative example provides a method for preparing a positive electrode active material, which is substantially the same as the steps of Example 1, except that the amount of Sb2Se3 added is 35000 ppm of the sodium-containing layered oxide.
[0076] Experimental example
[0077] The positive electrode active material, conductive agent (acetylene carbon black), and binder (polyvinylidene fluoride PVDF) prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 5 were respectively mixed at a mass ratio of 80:10:10, and 1-methyl-2-pyrrolidone (the mass ratio of the positive electrode active material to 1-methyl-2-pyrrolidone was 4:1) was added and ball-milled for 1 hour to prepare a slurry, which was evenly coated on an aluminum sheet, dried, pressed and cut into a positive electrode sheet, and a 1 mol / L NaClO4 PC solution was used as an electrolyte, and a metal sodium sheet was used as The negative electrode was assembled into a 2032 button cell, and the Siken test system was used for electrical performance testing. In the cut-off voltage range of 2.0-4.0V, the discharge specific capacity at 0.1C and 1C was tested, the test charge and discharge rate was 1C, and the number of cycles was 50 cycles; rate performance test: the charge and discharge cut-off voltage was 2.0-4.5V, the discharge capacity C1 under 1C conditions, the discharge capacity C2 under 0.1C conditions, the rate performance was C1 / C2, among which the sodium storage gram capacity was the first cycle discharge specific capacity. The results are shown in the table below.
[0078] Table 1 Test results of electrical properties of positive electrode active materials prepared in various embodiments and comparative examples
[0079]
[0080] As can be seen from the above table, the sodium storage gram capacity, cycle stability and rate performance of the positive electrode active materials prepared in Examples 1 to 4 are all good; the sodium storage gram capacity, cycle stability and rate performance of the positive electrode active material prepared in Comparative Example 1 are the worst, because only one sintering is performed to obtain a sodium-containing layered oxide, and no selenium antimony compound and carbon source are added for secondary sintering. The structure of the positive electrode active material is unstable during the charge and discharge process and is prone to side reactions with the electrolyte; the sodium storage gram capacity, cycle stability and rate performance of the positive electrode active material prepared in Comparative Example 2 are poor, because no selenium antimony compound is added, the internal mechanical stress cannot be effectively reduced, the development and diffusion of micro-scratches are hindered, and intergranular cracking is inhibited, resulting in poor structural stability of the positive electrode active material, the rate performance and cycle stability of the positive electrode active material cannot be improved, and the side reactions between the electrolyte and the positive electrode and the dehydrogenation of the organic solvent in the electrolyte cannot be inhibited; Comparative Example 3 The prepared positive electrode active material has poor sodium storage gram capacity, cycle stability and rate performance. This is because antimony selenide is replaced by selenium oxide with the same selenium content and antimony oxide with the same antimony content. The selenium and antimony elements cannot be effectively melted into secondary particles and evenly dispersed on the surface of the positive electrode active material particles, and the effect is deviated compared with antimony selenide; the positive electrode active material prepared in comparative example 4 has poor sodium storage gram capacity, cycle stability and rate performance. This is because the addition amount of Sb2Se3 is too low, which cannot effectively reduce the internal mechanical stress, hinder the development and diffusion of micro-scars, inhibit intergranular cracking, and cannot effectively inhibit the side reactions between the electrolyte and the positive electrode, and fails to achieve the desired effect; the positive electrode active material prepared in comparative example 5 has poor sodium storage gram capacity, cycle stability and rate performance. This is because the addition amount of Sb2Se3 is too high, which leads to the coating layer, which hinders the effective insertion and removal of sodium ions, resulting in material performance deviation.
[0081] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A positive electrode active material, It is characterized in that Includes sodium-containing layered oxides, selenium antimony compounds and carbon.
2. The positive electrode active material according to claim 1, It is characterized in that Based on the mass of the sodium-containing layered oxide, the mass percentage of selenium is 500ppm-15000ppm; and / or, The mass percentage content of antimony element is 200ppm-15500ppm; and / or, The mass percentage of carbon element is 700ppm-20000ppm.
3. The positive electrode active material according to claim 1 or 2, It is characterized in that The selenium antimony compound includes at least one of antimony selenide, antimony selenide sulfide, and selenoantimonate; and / or, The sodium-containing layered oxide contains a chemical formula of NaNi x Fe y Mn z O 2 A material, wherein 0<x<0.5, 0<y<0.5, 0<z<0.5, x+y+z=1; and / or, The sodium-containing layered oxide also includes additive elements; The additive element includes at least one of magnesium, aluminum, strontium, tungsten and yttrium; Based on the mass of the sodium-containing layered oxide, the mass percentage of the additive element is 500ppm-10000ppm.
4. A method for preparing a positive electrode active material, It is characterized in that The steps include: The sodium-containing layered oxide is mixed with a selenium antimony compound and a carbon source and then sintered once to obtain the product.
5. The method for preparing the positive electrode active material according to claim 4, It is characterized in that Based on the mass of the sodium-containing layered oxide, the mass percentage of the selenium antimony compound is 1000ppm-30000ppm; and / or, The mass percentage content of the carbon source is 1000ppm-20000ppm.
6. The method for preparing the positive electrode active material according to claim 4, It is characterized in that The primary sintering temperature is 600°C-1000°C, the sintering time is 6h-20h, and the sintering atmosphere is an inert gas; and / or, The selenium antimony compound includes at least one of antimony selenide, antimony selenide sulfide, and selenoantimonate; and / or, The chemical formula of antimony selenide is Sb 2 (S a ,Se 1-a ) 3 , where 0<a<1; and / or, The selenoantimonate includes V(1,2-dap) 2 Sb 3 , C 6 H 20 N 4 Sb 3 V.M 2 Sb(SeO 4 ) 3 wherein M comprises at least one of Na and K; and / or, The carbon source includes at least one of glucose, sucrose, soluble starch, cellulose, graphene, carbon nanotubes, conductive carbon black and acetylene black.
7. The method for preparing the positive electrode active material according to any one of claims 4 to 6, It is characterized in that The method for preparing the sodium-containing layered oxide comprises: mixing a sodium source with a ternary precursor and an additive and then performing secondary sintering; The sodium source is calculated as sodium element, and the molar ratio of the sodium element to the ternary precursor is 0.8-1.6:1; and / or, The sodium source includes at least one of sodium carbonate, sodium nitrate, sodium hydroxide and sodium sulfate; and / or, Based on the mass of the ternary precursor, the additive is calculated as the additive element, and the mass percentage content of the additive element is 500ppm-10000ppm; and / or, The additive comprises at least one of an oxide, hydroxide or salt of magnesium, aluminum, strontium, tungsten or yttrium; and / or, The chemical formula of the ternary precursor is Ni x Fe y Mn z (OH) 2 , wherein 0<x<0.5, 0<y<0.5, 0<z<0.5, x+y+z=1; and / or, The secondary sintering temperature is 600° C.-1000° C., the sintering time is 6 h-14 h, and the sintering atmosphere is air.
8. A positive electrode sheet, It is characterized in that include: A positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 3 or the positive electrode active material prepared by the preparation method according to any one of claims 4 to 7.
9. A secondary battery, It is characterized in that Including the positive electrode sheet as described in claim 8.
10. An electrical device, It is characterized in that A secondary battery comprising the secondary battery according to claim 9.
